peningkatan keterampilan membaca nyaring menggunakan model picture and picture fase B kelas III Sd Muahammadiyah Muara Bungo - Oktavia, Susi; Guswita, Reni; Avana, Nurlev (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
This study was a Classroom Action Research (CAR) conducted in third-grade students at Muhammadiyah Elementary School in Muara Bungo. The background of the study was the low reading-aloud ability of students, with an average initial score of 68, still below the school's minimum completion standard of 75. To address this problem, the Picture and Picture learning model was used with the aim of improving students' reading-aloud skills, particularly on weather topics. The study was conducted in two cycles, each encompassing planning, action, observation, and reflection. Sixteen students participated. Data collected consisted of qualitative and quantitative data. Qualitative data were obtained through observations of the model's implementation and students' reading-aloud activities. Quantitative data came from the results of students' reading-aloud tests. The results showed that the Picture and Picture model was implemented effectively. Students' reading-aloud test scores improved from cycle I to cycle II. In cycle I, student completion was 56%, increasing to 87% in cycle II, exceeding the completion standard. This improvement demonstrates that the Picture and Picture model is effective in improving students' reading aloud abilities. This model has also been shown to increase student engagement and focus during the learning process, thus helping them achieve optimal reading aloud skills.